2018
DOI: 10.1039/c7ob02597a
|View full text |Cite
|
Sign up to set email alerts
|

Convenient synthesis of 2-amino-3-(arylthio)indoles via the Rh-catalyzed reaction of 3-diazoindol-2-imines with thioesters

Abstract: 2-Amino-3-(arylthio)indoles were conveniently synthesized via the Rh(ii)-catalyzed C-S/N-C coupling reaction between 3-diazoindol-2-imines and thioesters. The products could be further oxidized to 2-amino-3-(arylsulfonyl)indoles by m-chloroperbenzoic acid and the N-sulfonyl group could be easily removed by reduction with SmI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…3-Diazoindolin-2imines 21 with electron-withdrawing or electrondonating substituents on aromatic ring reacted smoothly to afford the corresponding products 50 in good yields (Scheme 16). [23] In 2019, Wang and colleagues developed a sequential process to access 5H-pyrazino [2,3-b]indoles starting from 3-diazoindolin-2-imines 21 (Scheme 17). The multi-step procedure started from a rhodiumcatalyzed NÀ H insertion reaction of Rh-carbene with enamines 51, affording products 52 in high yields.…”
Section: -Diazoindol-2-imines As Starting Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…3-Diazoindolin-2imines 21 with electron-withdrawing or electrondonating substituents on aromatic ring reacted smoothly to afford the corresponding products 50 in good yields (Scheme 16). [23] In 2019, Wang and colleagues developed a sequential process to access 5H-pyrazino [2,3-b]indoles starting from 3-diazoindolin-2-imines 21 (Scheme 17). The multi-step procedure started from a rhodiumcatalyzed NÀ H insertion reaction of Rh-carbene with enamines 51, affording products 52 in high yields.…”
Section: -Diazoindol-2-imines As Starting Materialsmentioning
confidence: 99%
“…3‐Diazoindolin‐2‐imines 21 with electron‐withdrawing or electron‐donating substituents on aromatic ring reacted smoothly to afford the corresponding products 50 in good yields (Scheme 16). [23] …”
Section: ‐Diazoindol‐2‐imines As Starting Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[79] The substrate scope was broad with regard to both the starting materials and in this process a new C(sp ). [80] The products were obtained through a nucleophilic attack of sulfur atom onto Rh-carbene intermediate followed by 1,3migration of the acyl group. When, cyclic thioester 264 were examined under standard reaction conditions, 7,8-dihydrobenzo [7,8][1,4]thiazo-cino [3,2-b]indol-6(5H)-ones 266 were isolated in good yields.…”
Section: Insertion Reaction Of 3-diazoindolin-2-iminesmentioning
confidence: 99%
“…1b ). Although Wang et al reported an aromatic indolyl C(sp 2 )–S bond formation from the reaction of 3-diazoindol-2-imines with thioesters 56 , the formation of vinyl C(sp 2 )–S bond via the sulfonium ylides rearrangement of the reaction of sulfur-containing compounds with diazo compounds is still unknown.…”
Section: Introductionmentioning
confidence: 99%